Beyond arboviruses: A multicenter study to evaluate differential diagnosis of rash diseases and acute febrile illness cases in Rio de Janeiro, Brazil. - Arthur Daniel Rocha Alves; Jéssica Vasques Raposo; Rafaela Moraes Pereira de Sousa; Claudete Aparecida Araújo Cardoso; Pâmela Karla Simões de Freitas Costa; Julienne Martins Araújo; Sabrina Teresinha Alvim Barreiro; Clarisse da Silveira Bressan; Guilherme Amaral Calvet; Rogério Valls de Souza; Patrícia Brasil; Rita de Cássia Nasser Cubel Garcia; et al. (PLoS ONE, 2022)
Introduction A wide variety of viruses can cause rash diseases (RDs) or acute febrile illness (AFIs) in children, adolescents and adults; however, approximately 19% of RD cases and 40% of AFI cases remain without a defined etiology. Parvovirus B19 (B19V) and herpesvirus infection can also cause RD and/or AFI, and in some risk groups, these infections can become persistent (or latent) and may require hospital treatment. Since these infections do not have mandatory reporting, they can be hidden by other diseases, such as those caused by arboviruses (e.g., dengue virus). In this context, the aim of this study was to pursue the differential laboratory diagnoses of B19V and herpesvirus infections in patients with RD and AFI, without a defined etiology, seen in hospitals and/or reference centers for infectious diseases in Rio de Janeiro. Methods A total of 114 participants were enrolled in the study, including 54 children and 60 adults. B19V infection was assessed by real-time PCR (qPCR) and ELISA (anti-B19V IgM and IgG). EBV was assessed through qPCR, and betaherpesviruses (HCMV, HHV-6 and HHV-7) were assessed through multiplex qPCR. Sociodemographic and clinical data were obtained from the medical record data of these participants. Results The median age of children with RD was 2 years (interquartile range (IQR): 5), and 55.6% were male. Among adults with AFI, the median age was 38 years (IQR: 21), and 56.7% were female. Regarding RD patients, viral prevalence (and load) were 5.5%(104IU/mL), 3.4%(104IU/mL), 5.5%(104IU/mL) and 11.1%(105IU/mL) for B19V, EBV, HCMV and HHV-6 infection, respectively, and in AFI patients they were 6.6%(105IU/mL), 1.6%(103IU/mL), 3.3%(104IU/mL) for B19V, HCMV and HHV-6, respectively. HHV-7 was not detected in RD or AFI patients. Conclusion These results suggest the importance of including B19V and herpesviruses in the differential laboratory diagnoses for patients with RD and AFI, not only for epidemiological purposes but also for the proper management of the patient.